Boston keratoprosthesis type 1 - indication, complication and visual outcomes - Raina, Kritika; Gupta, Alka (International Journal of Research in Medical Sciences, 2017)
Background: Diseases affecting the cornea are a major cause of blindness all over the world, second only to cataract in overall importance. In India, there are approximately 6.8 million people who have corneal blindness with vision less than 6/60 in at least one eye, and of these, about 1 million have bilateral corneal blindness. Methods: The study was conducted in upgraded department of ophthalmology, L.L.R.M. Medical College, Meerut, India from January 2014 to June 2015. It was prospective interventional study. Included those patients who have Failed corneal graft with poor prognosis for further grafting, multiple corneal graft failure, having nearly total corneal neovascularization, vision less than 6/60 with associated other complications in better eye and no vision in opposite eye and Healed Chemical burn and those patients who has end stage glaucoma or RD (retinal detachment), defective perceptions and projection of light and not willing for the procedure. Results: A total of 20 patients were enrolled for the study which were followed up and assessed over 12 months. It was observed that maximum number of patients were in the age group of 41-60 years (45%) and in the >60 years group are minimum (20%). Among these 14 cases (70%) were male and 6 cases (30%) were female. Conclusions: The Boston type 1 keratoprosthesis provides visual recovery for eyes with multiple PK failures or with poor prognosis for primary PK, showing excellent retention rates. Most of the cases had a significant improvement in vision after Boston type I KPro implantation.